Investigating the effects of percussion massage therapy on pain, functionality, muscle diameter, and proprioception in ındividuals with ACL reconstruction: a randomized controlled trial - Beyza Nur Erayata; Burak Menek (PLoS ONE, 2025)
Background Percussion massage therapy (PMT) integrates traditional massage with vibration therapy. This study examined the effects of adding PMT to a structured exercise program for individuals who underwent surgery after an anterior cruciate ligament (ACL) injury. Methods A total of 24 individuals aged 18–40 were included in the study. Participants were divided into the PMT and structured exercise groups (SEG). The SEG group received a progressive neuromuscular exercise program, and the PMT group received the same structured exercise program and PMT. Range of motion (ROM) was assessed using the Goniometer Pro smartphone application, joint position sense (JPS) was measured goniometer, pain intensity was evaluated with the Visual Analog Scale (VAS), functionality was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), balance was measured with the Berg Balance Scale, quality of life was evaluated using the Short Form-36 (SF-36), and muscle diameter was measured via ultrasonography. Results Significant improvements were observed in all parameters in both groups post-treatment (p < 0.05). The PMT group showed superior results compared to the SEG group in ROM, JPS (60°), pain, functionality, balance, and quality of life (particularly in the general health perception sub-parameter of SF-36) (p < 0.05). Conclusions The findings of this study suggest that incorporating PMT, a novel approach in the literature, into the rehabilitation program following ACL reconstruction could be effective. PMT could be an alternative treatment method that can be used in conjunction with exercise programs in ACL rehabilitation. Trial Registiration NCT06185231.